PENELITIAN DAMPAK SOSIAL MEDIA INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI KONSUMEN - Ramadhan, Rifky; Aristianingrum, Yulia (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
In research on social media, it was concluded that social media is a platform that is widely used by various individuals, with Instagram being one of the frequently used social media. When analyzing purchasing interest, it was found that many people looked for information about various products via Instagram, which then generated purchasing interest and influenced purchasing decisions. In the analysis of purchasing decisions, it was found that Instagram has features that support consumers to make transactions on their platform which will increase consumer purchasing decisions to be stronger. From the results of the descriptive analysis of social media, it shows that respondents agree that social media encourages respondents to shop online. via the Instagram application, from the results of the descriptive analysis of purchasing interest, respondents agree that there is purchasing interest in shopping online via the Instagram application. From the results of the descriptive analysis of purchasing decisions, respondents agree that purchasing decisions encourage respondents to shop online via the Instagram application and can easily make transactions through the feature. -features in the Instagram application, from the results of hypothesis testing, there is a positive relationship between social media and consumer buying interest, and from the results of hypothesis testing, there is a positive relationship between buying interest and purchasing decisions.